2006
DOI: 10.1007/s00345-006-0126-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory factor analysis: strategies used by patients to promote health

Abstract: Strategies used by patients to promote health (SUPPH) was used to measure self-care self-efficacy in patients with cancer. The objectives of this study were (1) to determine the extent to which self-efficacy theory explained the factor structure of the SUPPH and (2) to determine the relationship of demographic data with factors of the SUPPH. Subjects were diagnosed with prostate cancer (PCa) and treated with either: (a) radical prostatectomy, (b) intensity modulated radiation therapy (IMRT) + radioactive seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…In men with prostate cancer, a growing body of research, focused on personal beliefs about exercising some control over conditions that affect one's life, demonstrated that self-efficacy may link psychological factors and outcomes such as QOL, symptom distress, stress, anxiety, and depression [14]. In survivors of PCa, higher self-efficacy was significantly (p=0.001) associated with better urinary, sexual, and bowel function [16].…”
Section: Introductionmentioning
confidence: 99%
“…In men with prostate cancer, a growing body of research, focused on personal beliefs about exercising some control over conditions that affect one's life, demonstrated that self-efficacy may link psychological factors and outcomes such as QOL, symptom distress, stress, anxiety, and depression [14]. In survivors of PCa, higher self-efficacy was significantly (p=0.001) associated with better urinary, sexual, and bowel function [16].…”
Section: Introductionmentioning
confidence: 99%
“…Three subscales (stress reduction, making decisions, and positive attitude) and a total score can be calculated. 42 An increase in score shows an increase in level of self-efficacy related to self-care behaviors. Disease-specific quality of life was assessed using the FACT-L scale.…”
Section: Data Collectionmentioning
confidence: 99%
“…Studies have suggested that those cancer patients who feel more efficacious in their ability to cope are better adjusted (4,20), enjoy a higher quality of life (21), may live longer (22), and experience less depression (23) than those who feel less confident in their ability to cope.…”
mentioning
confidence: 99%
“…Whereas self-efficacy for coping has been investigated in the more broad literature on health and illness, relatively few researchers have examined this construct fully as it relates to cancer. The few brief measures of coping self-efficacy that exist currently were not developed to the point of the CBI-L and therefore do not yet lend themselves to shortening at this point (18,20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation